EDUCAÇÃO PROFISSIONAL E SUA INTEGRAÇÃO COM A EDUCAÇÃO BÁSICA COMO ESPAÇO DE DISPUTA POLÍTICA / Professional Education and its integration with Basic Education as a place of policy dispute (Trabalho & Educação, 2016)
This article is a brief analysis of the historical process of Professional Education and its integration with Basic Education, considering the involved politics aspects and legislation. For this, we discuss some events that marked the Professional Education in Brazil, showing that the formation of the worker since the beginning been guided in the interests of the ruling class. In this sense, although the trajectory of Professional Education in the last twenty years has been subject of discussions and conflicts created by various sections of the working class to promote overcoming the duality and fragmentation existing between Professional Education and Basic Education, and despite the existence of Decree No. 5.154/04 overcoming duality and fragmentation did not occur. In this context, we discuss the realization of an integrated Professional Education with Basic Education and the role of the Federal Institutes as an opportunity to contribute to this perspective, with a view to training the working class with knowledge related to science, technology, and culture. Finally, it will be emphasized the challenges of vocational education as a polytechnic education.___O presente artigo trata de uma breve análise do processo histórico da Educação Profissional e de sua integração com a Educação Básica, considerando os aspectos políticos implicados e a legislação vigente. Para tanto, serão abordados alguns acontecimentos que marcaram a Educação Profissional no Brasil, evidenciando que a formação do trabalhador desde o início esteve pautada no interesse da classe dominante. Nesse sentido, embora a trajetória da Educação Profissional nos últimos 20 anos estivesse sujeita às discussões e aos embates promovidos por diversos setores da classe trabalhadora no sentido de promover a superação da dualidade e fragmentação existente entre a Educação Profissional e a Educação Básica, e apesar da vigência do Decreto n. 5.154/04, a superação da dualidade e fragmentação concretamente não ocorreu. Nesse contexto, será discutida a efetivação de uma Educação Profissional integrada com a Educação Básica e o papel dos Institutos Federais como uma possibilidade de contribuir para essa perspectiva, com vistas a uma formação da classe trabalhadora com conhecimentos relacionados à ciência, à tecnologia, à cultura. Por fim, serão enfatizados os desafios da Educação Profissional como uma formação politécnica.